A study on operational stressors among traffic police officers in Bengaluru - Faseeh K Mohiddina; Mohammed Hafeez; Emad Mir Abbas; Shivakumar B Raja; H R Aravinda Prabhu; Haleemath Thabsheera (Wolters Kluwer Medknow Publications, 2022)
Background: Occupational stress among police officers is extensive but neglected issue. It has number of negative consequences individually as well as on the department as a whole. Occupational stress is associated with physical and mental health-related issues, and are not addressed in Indian police officers with adequate importance. Objectives: The objective of this study was to identify the occupation-related stressors faced by traffic police officers in Bengaluru. Materials and Methods: Cross-sectional survey was conducted among police personnel in Bengaluru urban police district, Karnataka, India. Data were collected using a pretested structured questionnaire (operational police stress questionnaire). The data obtained was coded and entered into Microsoft Excel sheet. Descriptive and inferential analysis was carried out. Results: Six operational stressors were found to have a median value of 4 and above, which were negative comments from public, managing your social life outside of work, limitations to your social life, not enough time to spend with friends and family, feeling like you are always on the job and overtime demands. Among operational stressors, 76% (38) of the respondents marked a score of 4-7 for the stressor "Negative comments from public," which marked higher comparatively. Conclusion: The results point to a higher level of stress among traffic policemen, which needs attention from higher authorities. Stress management training needs to be given at regular intervals to improve their work efficacy and coping skills.